Granulomatous hepatitis in a Saudi child with defect: a case report and literature review - Meshari A. Alaifan; Ohood Abusharifah; Rana Yagoub Bokhary; Babajan Banaganapalli; Noor Ahmad Shaik; Naglaa M. Kamal; Omar I. Saadah (SAGE Publishing, 2022)
Interleukin-2 receptor alpha ( IL2RA ) defect (OMIM- # 606367) is an immune disease where affected patients are vulnerable to developing recurrent microbial infections in addition to lymphadenopathy and dermatological manifestations. This condition is known to be caused by pathogenic variants in the IL2RA gene, which are inherited in an autosomal recessive fashion. In this case report, we present a patient with IL2RA defect from Saudi Arabia who presented with chronic diarrhea, poor weight gain, mild villous atrophy, malnutrition, hepatomegaly, nonspecific inflammation, and an eczematous skin rash. His genetic analysis revealed a novel, homozygous, and likely pathogenic variant, that is, c.504 C>A (Cys168Ter), located in the exon 4of the IL2RA gene, which was inherited from his parents in an autosomal recessive mode of inheritance. This variant produces a 272-amino-acid shorter IL2RA protein chain, which most likely becomes degraded in the cytosol. Thus, we assume that the c.504 C>A is a null allele that abolishes the synthesis of IL2RA , malforms the IL-2 receptor complex, and eventually causes immunodeficiency manifestations. To our knowledge, this is the first time a person with IL2RA defect has shown signs of granulomatous hepatitis on a liver biopsy.